Tissue distribution and prevalence of Wolbachia infections in tsetse flies, Glossina spp - Cheng, Q; Ruel, T.D.; Zhou, W.; Moloo, S.K.; Majiwa, Phelix A.O.; O'Neill, S.L.; Aksoy, S. (Wiley, 2000)
Tsetse flies Glossina spp. (Diptera: Glossinidae) harbor three different symbiotic microorganisms one being an intracellular Rickettsia of the genus Wolbachia. This bacterium infects a wide range of arthropods, where it causes a variety of reproductive abnormalities, one of which is termed cytoplasmic incompatibility (CI) that, when expressed results in embryonic death due to disruptions in fertilization events. Here that in colonized flies, Wolbachia infections can be detected in 100 percent of sampled individuals, while infections vary significantly in field populations. Based on Wolbachia Surface Protein (wsp) gene sequence analysis, the infections associated with different fly species are all unique within the A group of the Wolbachia pipientis clade. In addition to being present in germ-line tissues, volbachia infections have been found in somatic tissues of several insects. Using a Wolbachia-specitic PCR-based assay, the tissue tropism of infections in Glossina morsitans morsitans Westwood. Glossina brevipalpis NEwstead and Glossina austeni Newstead were analysed. While infections in G. m. morsitans and G. brevipalpis were limited to reproductive tissues in G. austeni. Wolbachia could be detected in various somatic tissues.